2011
DOI: 10.1038/onc.2011.482
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of RPL11 at promoter sites of p53-regulated genes upon nucleolar stress through NEDD8 and in an Mdm2-dependent manner

Abstract: Ribosomal proteins (RPs) activate the p53 tumoursuppressor protein upon disruption of the nucleolus. However, the exact mechanisms for p53 transcriptional activation through RPs are not well understood. We show that the RPL11 is rapidly but transiently recruited at promoter sites of p53-regulated genes upon nucleolar stress induced by actinomycin D (ActD). Characterisation of molecular events at p53 promoter sites shows that L11 is required for the recruitment of p53 transcriptional co-activators p300/CBP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 49 publications
(62 reference statements)
0
70
0
Order By: Relevance
“…The human coilin-interacting nuclear ATPase protein (hCINAP), a protein essential for Cajal body formation, directly binds to RPS14 and inhibits RPS14 NEDDylation due to the recruitment of NEDP1 . Mechanistically, at least for RPL11, the observed relocalisation upon stress is accompanied with the recruitment of RPL11 to the transcription sites of p53-regulated genes, facilitating the recruitment of the p300 transcriptional co-activator and p53 activation (Mahata et al 2012).…”
Section: Nedd8 and Transcriptional Activity Regulation P53 And Tap73mentioning
confidence: 99%
“…The human coilin-interacting nuclear ATPase protein (hCINAP), a protein essential for Cajal body formation, directly binds to RPS14 and inhibits RPS14 NEDDylation due to the recruitment of NEDP1 . Mechanistically, at least for RPL11, the observed relocalisation upon stress is accompanied with the recruitment of RPL11 to the transcription sites of p53-regulated genes, facilitating the recruitment of the p300 transcriptional co-activator and p53 activation (Mahata et al 2012).…”
Section: Nedd8 and Transcriptional Activity Regulation P53 And Tap73mentioning
confidence: 99%
“…Upon actinomycin D treatment, a rapid decrease in L11 NEDDylation allows rapid but transient recruitment of L11 at the promoter of p53 target genes. L11 is required for the recruitment of p53 transcriptional co-activators p300/CBP and p53 K382 acetylation, thus activating the transcriptional activity of p53 (Mahata et al, 2012) (Figure 1D). Therefore, RPs participate in the regulation of p53 activation by diverse mechanisms.…”
Section: Major Mechanisms That Mediate Extra-ribosomal Functions Of Rmentioning
confidence: 99%
“…8 The following factors have been identified: p300/ CBP 26 acetylates p53 to increase p53 stability and activity; SOX4 is an important p53 regulator in the cellular response to DNA damage; 6 MYBBP1A enhances the interaction between p53 and p300, which promotes p53 acetylation in response to ribosomal stress; 27 and RPL11 is required for p53 acetylation and p300 recruitment to the promoter regions of the p53 target gene in response to ribosomal stress. 28 In this study, we found that NLK binds to not only p53 but also to MDM2, and NLK stabilizes p53 by abrogating the p53-MDM2 interaction. We also found that NLK inhibits MDM2-mediated ubiquitination of p53 and promotes p53 acetylation at Lys382, and this modification increases p53 activity by increasing the DNAbinding ability of p53.…”
Section: Discussionmentioning
confidence: 48%